Peran Lembaga Pendidikan dalam Membentuk Karakter Peserta Didik Era 4.0 di Sekolah Indonesia Kuala Lumpur - Dwi Indah Cahyani; M Fiqri Fadhilah; Muhammad Fiqri Fadhilah; Sayyidatul Wachidah; Elya Umi Hanik (JEID: Journal of Educational Integration and Development, 2021)
Character is a very important personality and morals and is needed by students to become better human beings and have good character. Character is one of the things that is closely related to educational goals. Education has its own challenges in paying attention to the character of students in an increasingly developing era until the 4.0 era. along with the development of the times sometimes makes a person forget his identity as a human being and forget about the values ? of his character. This study aims to determine how the role of educational institutions in shaping the character of students in the era 4.0 at Kuala Lumpur Indonesian School. This type of research uses qualitative research. Data collection techniques used in this study were interview data analysis via email. The results of this study are to explain that the development of that era is increasingly developing until the era of 4.0. In the 4.0 era, it is very important to instill character in students. The role of SIKL educational institutions in shaping the character of students is by embedding characters that have been promoted since kindergarten and framed in various forms of activities such as an honesty canteen. It is hoped that students are able to practice and practice honesty values ??in everyday life. Keywords: role of educational institutions, character, era 4.0